Pemikiran politik Islam : dari masa klasik hingga Indonesia kontemporer - Iqbal, Muhammad, 1968-; Nasution, Amin Husein (Rawamangun, Jakarta : Kencana, 2010)
History and development of political thought of Islam in Indonesia.
Includes bibliographical references (p. [323]-336) and index.
Keywords: Islam and politics -- Indonesia; Indonesia -- Politics and government